2008
DOI: 10.1192/bjp.bp.106.029009
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal studies of cognition in schizophrenia: Meta-analysis

Abstract: Participants with schizophrenia displayed improvement in most cognitive tasks, but practice was more likely than cognitive remediation to account for most of the improvements observed. Semantic verbal fluency may be the best candidate cognitive endophenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
189
3
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(216 citation statements)
references
References 69 publications
17
189
3
6
Order By: Relevance
“…Several studies have provided evidence indicating that cognitive and intellectual deficits are evident early in neurodevelopment, well before the onset of psychosis (Fuller et al 2002;Reichenberg et al 2010;Kahn & Keefe, 2013). Evidence also suggests that cognitive deficits are stable at follow-up in both chronic and early years of the illness even though performance of schizophrenia patients might improve less than healthy controls at follow-up (Szöke et al 2008;Bora & Murray, 2013;Hedman et al 2013). Neurodevelopmental theories argue that schizophrenia is related to genetic and non-genetic risk factors leading to abnormal development of the brain that can be associated with problems in acquiring cognitive abilities throughout development (Weinberger, 1986;Murray & Lewis, 1987), and that neurodevelopmental abnormality can be considered as the source of most of the cognitive deficits observed in adults with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have provided evidence indicating that cognitive and intellectual deficits are evident early in neurodevelopment, well before the onset of psychosis (Fuller et al 2002;Reichenberg et al 2010;Kahn & Keefe, 2013). Evidence also suggests that cognitive deficits are stable at follow-up in both chronic and early years of the illness even though performance of schizophrenia patients might improve less than healthy controls at follow-up (Szöke et al 2008;Bora & Murray, 2013;Hedman et al 2013). Neurodevelopmental theories argue that schizophrenia is related to genetic and non-genetic risk factors leading to abnormal development of the brain that can be associated with problems in acquiring cognitive abilities throughout development (Weinberger, 1986;Murray & Lewis, 1987), and that neurodevelopmental abnormality can be considered as the source of most of the cognitive deficits observed in adults with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical high-risk populations, category fluency deficits-among the largest and most stable neurocognitive impairments in schizophrenia (Bokat & Goldberg, 2004;Szoke et al, 2008) -have shown promise as a clinical risk marker for psychosis (Becker et al, 2010;Eastvold, Heaton, & Cadenhead, 2007;Hawkins et al, 2004). The evidence is less clear, however, for using category fluency deficits as a clinical risk marker in psychometric schizotypy-a group at putative high risk for psychotic and other psychiatric disorders (Lenzenweger, 2006;Meehl, 1990; see Chun, Minor, & Cohen, 2013).…”
mentioning
confidence: 99%
“…[6][7] However, inconsistent data are available whether the research results based on patients in early stages of the illness can be generalized on more geriatric populations. 5,[8][9][10][11] Today, only few evaluated therapy approaches are available for middle-aged and older schizophrenia patients focusing on the defined treatment targets. A recent review 1 identified three social skills therapy approaches (SST) for elderly people with schizophrenia: the Functional Adaptation Skills Training 12 (FAST), Helping Older People Experience Success 13 (HOPES), and the Cognitive Behavioral Social Skills Training 14 (CBSST), which combines SST with cognitive-behavioral therapy.…”
mentioning
confidence: 99%